(untitled) (Bangladesh Journal of Botany, 2020)
The chemical compositions of the hydrodistilled essential oils of ripen and unripen berries of Juniperus macrocarpa Sibth. & Sm. (Jom) were analysed by GC-MS. Thirty eight compounds were identified from unripe berries, accounting for approximately 0.03% oil yield (v/w dried weight) and 16 compounds from ripe berries with 0.003% oil yield (v/w dried weight). While the major compounds in the essential oils of unripe berries were α-cedrol (30.04%), α-pinene (18.81%), germacrene-D (14.58%), δ-cadinene (3.80%), γ-cadinene (2.29%), α-humulene (2.29%), γ-muurolene (2.27%), epi-bicyclosesquiphellandrene (1.69%), transcaryophyllene (1.68%), valencen (1.53 %) and α-cedrol (49.87%), β- caryophyllene (29.57%), α-cedrene (4.75%), γ-muurolene (2.54%), carvacrol methyl ether (1.4%), trans-pinocarveol (1.2%), α-pinene (1.13%), α-muurolene (1.04%) were identified from ripe berries and their mean percentage varied according to their phenological stage. Both qualitative and quantitative differences between ripe and unripe berries of the plant were observed.